COPING STRATEGY LANJUT USIA DALAM MEMENUHI KEBUTUHAN DASAR PADA MASA PANDEMI COVID-19 - Popon Sutarsih; Nurrohmi (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2022)
Coping strategy is defined as management of behaviour on the problem solving in the simplest and most realistic way and its function is to avoid from the real and unreal problem. Coping strategy aims to overcome, decrease, and resist from the demands cognitively and in the form of behaviour. The purpose of research is to describe coping strategy of elderly in meeting basic needs which involves emotional-focused copingconsisting of seeking social emotional support, distancing, escape avoidance, selfcontrol, accepting responsibility, positive reappraisal aspects and problem-focused coping that consist of seeking informational support, confrontive coping, planful-problem solving aspects. Method used was descriptive method and quantitative approach. Collection data was implemented by delivering questionnaires, as the primary source data, and using documents as secondary source data. The sampling technique used was simple random sampling with the number of populations was 450 respondents. Research data were analyzed by employing quantitative analysis. The research result, in general, indicated that coping strategy of the elderly in meeting the basic needs in the PandemicCovid-19 period at the Mangunarga Village, Cimenyan Sub-District, Sumedang Disrict, was on the medium category. This is meant that those elderly had used coping strategy quite well, primarily aspect of the problem-focused coping.